A Bionic Self-Assembly Hydrogel Constructed by Peptides With Favorable Biosecurity, Rapid Hemostasis and Antibacterial Property for Wound Healing - Wang, Yang; Li, Xiao; Yuan, Juzheng; Wang, Xudan; Tao, Kaishan; Yan, Jin (Frontiers in Bioengineering and Biotechnology, 2022)
Bionic self-assembly hydrogel derived by peptide as an effective biomedical hemostatic agent has always gained great attention. However, developing hydrogels with eminent-biosecurity, rapidly hemostatic and bactericidal function remains a critical challenge. Hence, we designed an injectable hydrogel with hemostatic and bactericidal function based on Bionic Self-Assembling Peptide (BSAP) in this study. BSAP was formed with two functionalized peptides and possessed the ability of self-assembly into nanofibers originating from (RADA)4 motif. As expected, BSAP could rapidly co-assembled into network and formed hydrogel in situ driven by Ca2+. The hydrogel with concentration of 5% shows better microporous structure and good shear thinning property with injectability suitable. Moreover, the fabricated hydrogel exhibited lower blood clotting index and significantly reduce the blood clotting time and blood loss in foot trauma model and tail amputation model. Remarkably, the hydrogels reduced the inflammatory responses by blocking the bacteria infection, and thus promoted the wound healing. Finally, the hydrogel was demonstrated excellent hemocompatibility and had no cytotoxicity. Overall, this work provides a strategy for developing a high-biosecurity hydrogel with hemostatic and antibacterial properties, which will enable the clinical application of BSAP.